Etiological indicators of the Simmental breed of cattle - Kurbonova Sh.E; Nurmukhammedova R.F; Sayfullaeva Yu.Z (Zien Journals, 2022)
The article presents data on the ethological indicators of Simmental cattle at the age of 6 and 18 months (standing, chewing, eating, sleeping, general activity index).
Keywords: cattle; Simmental breed; ethological indicators; general activity index